If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + -2 + -12b = 0 Reorder the terms: -2 + 7b + -12b = 0 Combine like terms: 7b + -12b = -5b -2 + -5b = 0 Solving -2 + -5b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5b = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5b = 0 + 2 -5b = 0 + 2 Combine like terms: 0 + 2 = 2 -5b = 2 Divide each side by '-5'. b = -0.4 Simplifying b = -0.4
| 7x-(x-5)= | | 6(3n-8)-5(2n+7)= | | 3r+12/6=4r-4/4 | | X^2-5x=9-3x^2 | | 8x+12-5x-9= | | 8x+2=8(x+4) | | 5/2x=15/12 | | 3x+11-6x=15-14x+11x-4 | | 3(2x+1)-5=6x-2 | | 0.06(y-9)+0.04y=0.08y-0.01(60) | | 1/3+10u=y/v | | 6=-2910n+7 | | 8-(3+7)=23 | | 0.4x+56000(0.2+x)=1400 | | B=xm+m | | 2y^3+2+6y^2+6y= | | 4(3+5x)=47 | | 5p-13=8p+4 | | 5x-3+3(2x+2)=-3(x+3) | | tn=5n+7 | | 7x+8x=13x | | 6x+7-2x=19 | | 5x+7(x-1)=-3 | | 2y-6=2x | | 5a+10=3a+10 | | x+(x*0.07)=35.19 | | 14(t-6)+4t=6(3t+5)-8 | | (6x-6)-(13x+8)= | | 3x-5(x-3)=16-4x | | x+(x*0.07)=28.25 | | -13x=234 | | -(4y+4)-(-3y-8)=-2 |